Fourteen polymorphic microsatellite markers for a widespread limestone endemic, Carex eburnea (Cyperaceae: Carex sect. Albae)1. (21st August 2017) - Gillespie, Emily L.; Pauley, Annabella G.; Haffner, Megan L.; Hay, Nikolai M.; Estep, Matt C.; Murrell, Zack E.
Abstract : Premise of the study: Microsatellite primers were developed for a widespread limestone endemic sedge, Carex eburnea, to facilitate investigation of the genetic diversity and phylogeography of this taxon and its closest relative, C. mckittrickensis . Methods and Results: Forty‐eight primer pairs were designed from Illumina sequence data and screened for suitability. Fourteen of these primer pairs were polymorphic and generated one to seven alleles per locus. Cross‐species amplifications were conducted for all four members of Carex sect. Albae . Conclusions: These primer pairs can be used to assess the genetic diversity and population structure in future studies of C. eburnea and C. mckittrickensis, and likely in other members of Carex sect. Albae .